1987
DOI: 10.1017/s0143385700004132
|View full text |Cite
|
Sign up to set email alerts
|

A bound for the fixed point index of area-preserving homeomorphisms of two-manifolds

Abstract: The study of area preserving maps of manifolds has an extensive history in the theory of dynamical systems. One interest has been in the behaviour of such maps near an isolated fixed point. In 1974 Carl Simon proved the existence of an upper bound for the index of an isolated fixed point for Ck area preserving diffeomorphisms of a surface. We extend his result to homeomorphisms of an orientable two manifold. The proof utilizes the notion of free modification, developed by Morton Brown, and enlarges the scope o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
5

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 2 publications
0
13
0
5
Order By: Relevance
“…If we drop the hypothesis about isolation of the fixed point, it remains true for the planar case that the index of a fixed point is less than or equal to 1 Provided that the homeomorphism is area-preserving. This result was proved by Pelikan and Slaminka in [PS87]. Previously, Nikishin and Simon had addressed the same question for diffeomorphisms, see [Ni74] and [Si74].…”
Section: Franks Introduced Conley Index Techniques Inmentioning
confidence: 72%
“…If we drop the hypothesis about isolation of the fixed point, it remains true for the planar case that the index of a fixed point is less than or equal to 1 Provided that the homeomorphism is area-preserving. This result was proved by Pelikan and Slaminka in [PS87]. Previously, Nikishin and Simon had addressed the same question for diffeomorphisms, see [Ni74] and [Si74].…”
Section: Franks Introduced Conley Index Techniques Inmentioning
confidence: 72%
“…Le Calvez [5] showed that if the associated fixed point index is greater than one, then there is a wandering domain in any neighborhood of that point. In particular, should the homeomorphism be area-preserving, this index must be lower or equal than one, a former result by Pelikan and Slaminka [8]. In the case of stable fixed points, Dancer and Ortega [2] showed this index to be exactly one; it immediately implies that isolated minimizers are unstable because they are well known to have fixed point index minus one.…”
Section: Introductionmentioning
confidence: 87%
“…This operation produces lots of periodic points which accumulate in the fixed one. Incidentally, notice that, in contrast, if the map is a homeomorphism and the fixed point is accumulated by Per(f ) but not by Fix(f n ) then i(f n , p) = 1 (see [PS87] and also [L03], pag. 145).…”
Section: Introductionmentioning
confidence: 99%